PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK WISATA DI BLIBLI TRAVEL PADA MASA PANDEMI COVID-19 - ., Viona; Eka Mahadewi, Ni Putu; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023)DO - 10.24843/IPTA.2023.v11.i01.p19, 2023)
This research is conducted because the marketing mix strategy applied by Blibli Travel was ineffective. This study aims to determine the effect of the 7P marketing mix (product, price, place, promotion, people, process, and physical evidence) and which marketing mix had the most significant influence on tourism products purchasing decisions at Blibli Travel during the Covid-19 pandemic. This sample is determined by purposive sampling method with total sample of 125 respondents. Data collection uses questionnaires distributed online through social media, interviews with Blibli Travel management and several Blibli Travel consumers, observations, literature studies, and documentation. The data analysis technique is descriptive quantitative with validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination test. This study uses the IBM SPSS Statistics 25 for MacOS program. The results indicate that product and physical evidence partially have a significant effect on tourism products purchase decision at Blibli Travel while price, place, promotion, people, and process partially have no significant effect on tourism products purchase decision at Blibli Travel. Meanwhile, simultaneously, the marketing mix has a significant effect on tourism products purchase decision at Blibli Travel with a coefficient of determination of 69%.